Exploring the Availability and Utilisation of Modern Resources for Teaching Life Sciences in Some Selected Schools in South Africa - Adu, Kemi O.; Mtsi, N. (Journal of Ecohumanism, 2024)
Life sciences in South Africa cover a broad range of disciplines and have significant contributions in both academic and practical fields. This paper explores the availability and utilization of modern resources for teaching Life Sciences in some selected schools in South Africa. The study employs a transformative paradigm of qualitative research using a phenomenological case study design. Eight teachers were purposively selected and the data were analysed using a thematic approach. The findings revealed among others that without modern resources the teaching and learning of Life Sciences will be a mirage and teachers will find it difficult to disseminate the contents of the subject and achieving learning outcomes will not be possible. The study concludes that Life Sciences teachers need to employ the use of modern resources to meet the needs of the learners in the 21st century. It was recommended that the teacher should update their knowledge in the use of modern resources for teaching Life Sciences and resources should be used following the subject matter and the grade level of the learners.